DAMPAK KETERLIBATAN DAN DUKUNGAN MASYARAKAT PADA WISATA SPIRITUAL DI BALI-INDONESIA - Ida Bagus Nyoman Weda (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
Spiritual tourism is a form of tourism that is growing rapidly in the Province of Bali, so it needs to be developed as a sustainable tourist destination. In order to support the successful implementation of the sustainable tourism program, the participation of the existing community is obtained and involved in the spiritual tourism. Based on these reviews, this study aims to examine and analyze the influence of community involvement, citizen support, and usefulness on the sustainability of spiritual tourism in Bali, Indonesia. This research is associative quantitative research with data collection techniques through survey methods with questionnaire media. Questionnaires were distributed to 90 residents who were involved in spiritual tourism in Bali-Indonesia which were then analyzed using PLS analysis. The results of the study concluded that community involvement and community support had a significant effect on usefulness. Community involvement and usefulness have a significant effect on the sustainability of the destination. However, community support has no significant effect on the sustainability of the destination.